Meeting students’ needs: teachers’ practice of multiple intelligences in English as second language classrooms - Ariffin, Kamisah; Husin, Misyana Susanti; De Mello, Geraldine; Ibrahim, Mohammad Nor Afandi; Omar, Nur Hidayatulshima; Ishak, Nurhamizah (Institute of Advanced Engineering and Science, 2024)
The multiple intelligence (MI) theory suggests that students learn in different ways based on their intelligence strengths, thus, proposes teachers employ a variety of intelligences to engage students in the teaching and learning process. This study explores the application of MI in the Malaysian English as second language (ESL) classrooms and the extent to which teachers provide instructions that meet the needs of the students in the classroom. Data were procured from a survey questionnaire that gauged teachers’ teaching activities in ESL classrooms under Gardner’s eight constructs of MI: linguistic, logical-mathematical, spatial, interpersonal, intrapersonal, bodily-kinesthetic, naturalist, and musical. Descriptive statistics using mean score and independent sample t-test was employed in the data analysis procedures. The findings reveal that only 58% of the teachers had knowledge of the MI theory, with only 12% having received formal pedagogical training on MI. In addition, the eight intelligences were not practiced equally. Interpersonal, linguistic, intrapersonal, and spatial intelligences seemed to be the most common strategies employed by teachers in their teaching as these MI are usually measured in the standardized tests while naturalistic and musical intelligences were the least frequently integrated as they are not included in the assessment scale in ESL. Such findings have significant pedagogical implications as classroom teachers should acknowledge the different levels of strengths and motivations in learning among the students. The study highlights the need to provide teachers with training and integrating personalized learning, utilizing students’ strong aspects, and employing a variety of teaching methods in the classroom.